Strategi Pengembangan Pariwisata Alternatif Berbasis Pelestarian Minuman Arak Bali di Desa Les, Kecamatan Tejakula, Buleleng - Arcana, I nyoman; Widuri, Setyowati Ayu; Suastuti, Ni Luh; Wiratnaya, I Nyoman (JURNAL GASTRONOMI INDONESIA, 2023)
This study aims to examine feasible development strategies for the development of alternative tourism based on the preservation of Bali Arak Drink in Les Village, Tejakula, Buleleng using a SWOT analysis. There are two groups of respondents, the first is tourists totaling 125 people, and the second is the stakeholder group totaling 25 people. Data collection through questionnaire dissemination.  This study concludes that the strength factors include: the cultural traditions, arak production process, Balinese food and arak pairing, natural attractions, close to the Tulamben, and souvenirs. The weaknesses include: lack of social media promotion, regulation and sales licenses. The opportunities include: the economy post Covid-19 Pandemic, the ease of bank credit, alcohol testing technology and product standardization. Threat factors are: the increases of fuel price, world geopolitics, licensing of spirits production, and enthusiasts of the younger generation to cultivate palm plantations. This research recommend to developing tour packages in the form of glamping in the coconut plantation area, Balinese culinary and educational tour packages, collaborations with influencers.